INTERAKSI SOSIAL PESERTA DIDIK AUTIS DI SEKOLAH INKLUSIF - Marya Ulfah, Isroatul (Jurnal Pendidikan Khusus, 2015)
ABSTRACT Every individual always requires others and it will form a social interaction among those who influence one another. Children with autism have three problems in their development namely behavior, communication, and social interaction. This study aims to describe a social interaction among the students with autism in inclusive elementary shcool of YBPK Semampir Kediri. This study used a qualitative research approach. It used interviews, observation, and documentation as data collection techniques. The result of this study indicated that the social interaction that existed among the students with autism including passive interaction was only being able to accept the approach of others and not being able to interact on a reciprocal basis. Judging from the factors that support the formation of social interaction (imitation, suggestion, identification, and sympathy) on the subject of the study, it suggested that social of research subject was still limited and not able to perform mutual communication. It can be said that social interaction among students with autism has been formed, but it was still in the passive or minimal category. Keywords : Social Interaction